2016
DOI: 10.1159/000445610
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Morocco Carob Honey Against Lead-Induced Anemia and Hepato-Renal Toxicity

Abstract: Background/Aims: Natural honey has many biological activities including protective effect against toxic materials. The aim of this study was to evaluate the protective effect of carob honey against lead-induced hepato-renal toxicity and lead-induced anemia in rabbits. Methods: Twenty four male rabbits were allocated into four groups six rabbits each; group 1: control group, received distilled water (0.1 ml / kg.b.wt /daily); group 2: received oral lead acetate (2 g/kg.b.wt/daily); group 3: treated with oral ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Honey reduced the cardiovascular risk factors and has many effects on several metabolic factors. Recently clinical research was also carried out about honey and concluded that honey provide a defensive effect from lead-induced blood, hepatic renal toxic effects (Fihri et al, 2016).…”
Section: Medicinal Value Of Honeymentioning
confidence: 99%
“…Honey reduced the cardiovascular risk factors and has many effects on several metabolic factors. Recently clinical research was also carried out about honey and concluded that honey provide a defensive effect from lead-induced blood, hepatic renal toxic effects (Fihri et al, 2016).…”
Section: Medicinal Value Of Honeymentioning
confidence: 99%
“…Interestingly, honey ingestion did not cause hypokalemia in spite of increased urine potassium and urine volume. In kidney diseases, Moroccan carob honey has a protective effect against lead-induced toxicity in rats; it ameliorated the elevation of serum creatinine and blood urea nitrogen induced by lead [ 9 ]. In addition, it was demonstrated that honey collected in the United Arab Emirates can protect liver and kidney during acute blood loss, food restriction, and after carbon tetrachloride intoxication [ 10 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for these findings is probably due to the specific conditions of the research units (the hemodialysis patients), but not due to the type of intervention (thyme honey), resulting in no effect of the intervention. Most previous studies that reported the positive effects of honey administration on slightly or significantly elevated hemoglobin levels mainly used amber and dark honeys, such as Manuka, Tualang, Clover and Carob honey (16,17,21). These honeys have high levels of phenolic compounds, minerals (iron, copper, etc) and antioxidant properties, which have hepatoprotective effects and positive effects on red blood cell production by stimulating bone marrow (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies that reported the positive effects of honey administration on slightly or significantly elevated hemoglobin levels mainly used amber and dark honeys, such as Manuka, Tualang, Clover and Carob honey (16,17,21). These honeys have high levels of phenolic compounds, minerals (iron, copper, etc) and antioxidant properties, which have hepatoprotective effects and positive effects on red blood cell production by stimulating bone marrow (17). The reason for the significant decrease in hemoglobin level in the study by Aliyu et al (2012) in Pakistan can be attributed to the type of honey used, the acacia honey with watery white color (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation